Moderation-Based Tafsir and Hadith Literacy Model: A Case Study in Traditional Pesantren of West Java for Character Development - Abdurrohman, Irwan; Ismail, Ecep (Diroyah : Jurnal Studi Ilmu Hadis, 2024)
A significant area of study in Islamic boarding schools, including those in West Java, is the Qur'an and Hadith of the Prophet (SAW).This study aims to analyse the moderation-based literacy model in Qur Bostanic and Hadith education in traditional pesantrens in West Java.Using a qualitative descriptive approach, data were collected through observations and interviews at three pesantrens: Raudat al-Muta'alimīn, Nur al-Hidayah, and Syams al-‘Ulūm. The findings indicate that pesantrens adopt non-radical teaching methods, such as sorogan, balaghan, and pasaran, fostering a moderate religious perspective among santri. This study provides insights into how pesantrens can play a role in strengthening moderate Islamic character. The literacy of tafsir and hadith used by kiyai and ustaz, and followed by their santri using sorogan, balaghan, and market teaching models of sources/references (books) written by scholars, is not known to be radical.The attitude of santri does not show any radicalist-fundamentalist potential; they follow what is taught by the kiyai or ajengan in the pesantren rather than listening to and following religious discourses from outside